Análise da dinâmica da desigualdade de renda no Brasil - Fernandes, Valdeci Evangelista (2015)
This work has the purpose of investigating the dynamic regarding income inequality in Brazil in the period ranging from 1976 to 2012, where the representativeness of the change on per capita income inequality behavior driven by national, regional and local aspects was analyzed. For this, a regression model with panel data was utilized, along with Bayesian techniques application, on which a new estimation was performed after inserting new factors in the group of existent factors. Apart from the policies concerning income distribution, educational levels, real gains for minimum wage and economic growth, factors that have some degree of impact on per capita income inequality were analyzed as well. It could be concluded that states in the South, Southeast and Center West have more representative variables linked to the common national factor, to the detriment of the variables linked to the common regional factor, which is more relevant to the northern and northeastern states. Just the same, in the national variance decomposition, the strongest impact on inequality of local income is determined by the national factor for the South states, while in the regional variance decomposition the strongest impact on the local per capita income inequality is due to the northern states.